1998
DOI: 10.1159/000012254
|View full text |Cite
|
Sign up to set email alerts
|

Psychometric Characteristics of the Somatoform Dissociation Questionnaire: A Replication Study<footref rid="foot01"><sup>1</sup></footref>

Abstract: Background: The present study aimed to replicate the results of previous studies concerning the development of two versions of the Somatoform Dissociation Questionnaire. The SDQ-20 evaluates the severity of somatoform dissociative phenomena, and the SDQ-5 is a dissociative disorders screening instrument. Methods: Thirty-one patients with dissociative disorders and 45 consecutive psychiatric outpatients with other DSM-IV diagnoses completed the SDQ-20 and SDQ-5 as well as the Dissociation Questionnaire which me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
31
0

Year Published

1998
1998
2018
2018

Publication Types

Select...
7
2
1

Relationship

3
7

Authors

Journals

citations
Cited by 101 publications
(33 citation statements)
references
References 13 publications
2
31
0
Order By: Relevance
“…The Somatoform Dissociation Questionnaire-5 [28] was used to determine the degree of dissociation. Suicidal ideation was determined with the Dutch adaptation of the Suicidality Questionnaire [29].…”
Section: Methodsmentioning
confidence: 99%
“…The Somatoform Dissociation Questionnaire-5 [28] was used to determine the degree of dissociation. Suicidal ideation was determined with the Dutch adaptation of the Suicidality Questionnaire [29].…”
Section: Methodsmentioning
confidence: 99%
“…The threatening nature of a terminal illness or of an EOL discussion may trigger a dissociative response in some patients that manifests itself as emotional numbness. 9, 10 The fourth edition of the Diagnostic and Statistical Manual of Mental Disorders (DSM–IV) 11 (p. 519) defines dissociation as “a disruption in the usually integrated function of consciousness, memory, identity, or perception of the environment.” Dissociation and emotional numbness impose psychological barriers to normal human interactions. Gershuny and Thayer assert that “when emotional pain is acute and deemed unbearable by the sufferer, dissociation may be called upon as a means of escape.” 12 (p. 647) In dissociative responses to psychological threats, symptoms of “freezing, analgesia, and emotional numbing” are believed to be elicited automatically.…”
Section: Introductionmentioning
confidence: 99%
“…Several authors report convincing clinical, theoretical, and research findings which support the case for a separate somatofom dissociative category (Kihlstrom, 1994;Nemiah, 1991;Nijenhuis et al, 1996Nijenhuis et al, , 1998a. Nijenhuis et al (1996Nijenhuis et al ( , 1998a found that somatoform dissociative phenomena, such as intermittent analgesia, anesthesia, motoric inhibitions, and pain symptoms, highly characterized dissociative disorder patients.…”
mentioning
confidence: 96%